An experimental study on evacuation dynamics including individuals with simulated disabilities. (November 2022) - Fu, Libi; Qin, Huigui; Shi, Qingxin; Zhang, Ying; Shi, Yongqian
Highlights: A controlled experiment was conducted to study evacuation dynamics of individuals with and without simulated disabilities. Evacuation time in tests with simulated wheelchair users and pedestrians on crutches is higher. Congestion near the exit formed slower in tests with individuals with simulated disabilities. Crowd danger is higher in the tests involving individuals with simulated disabilities. Abstract: This paper aims to measure the effect of individuals with simulated disabilities on evacuation processes in a room with an exit through a controlled experiment. A total of 60 individuals participated in the experiment. There are three mixed ratios (i.e., 0%, 5% and 10%) of users of two mobility aids (i.e., wheelchair users and pedestrians on crutches simulated by non-disabled pedestrians using auxiliaries). Video recordings and the Mean-shift algorithm are employed to extract and track pedestrians' trajectories. Evacuation time, speed, evacuation sequence and specific flow are analyzed according to the trajectories. It is discovered that compared with tests without individuals with simulated disabilities, evacuation time in tests with simulated wheelchair users and pedestrians on crutches increases, while the average instantaneous speed and specific flow decrease. The spatial distribution obtained by the Nearest-neighbor analysis suggests that congestion near the exit formed slower in tests with individuals with simulated disabilities. It is found that compared with tests without individuals with simulated disabilities, crowd danger is higher in the tests involving individuals with simulated disabilities, especially with simulated wheelchair users. It is hoped that this study will be helpful in crowd management involving individuals with disabilities.